1993
DOI: 10.1016/0735-1097(93)90381-a
|View full text |Cite
|
Sign up to set email alerts
|

The signal-averaged P wave duration: A rapid and noninvasive marker of risk of atrial fibrillation

Abstract: A prolonged signal-averaged P wave duration may be a simple noninvasive marker of the risk for development of atrial fibrillation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
102
2
1

Year Published

1993
1993
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 212 publications
(108 citation statements)
references
References 22 publications
3
102
2
1
Order By: Relevance
“…In addition to measuring P-wave duration on the standard surface leads, Guidera and Steinberg reported that the P-wave duration measured from the signalaveraged ECG (SA-ECG) was predictive of AF. 21 The SA-ECG is measured using 3 unique orthogonal ECG leads and the P-wave is averaged over a large number of cardiac cycles (range 84-842 beats) to reduce noise and amplify the portions of the P-wave that may not be visible on the 12-lead ECG.…”
Section: Study Limitationsmentioning
confidence: 99%
“…In addition to measuring P-wave duration on the standard surface leads, Guidera and Steinberg reported that the P-wave duration measured from the signalaveraged ECG (SA-ECG) was predictive of AF. 21 The SA-ECG is measured using 3 unique orthogonal ECG leads and the P-wave is averaged over a large number of cardiac cycles (range 84-842 beats) to reduce noise and amplify the portions of the P-wave that may not be visible on the 12-lead ECG.…”
Section: Study Limitationsmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] The utility of this technique rests on the premise that since AF is reentrant tachycardia, areas of slow and fractionated conduction are probably required. Averaging of high-resolution P waves could potentially identify the "atrial late potentials" in a manner akin to ventricular late potentials.…”
Section: Introductionmentioning
confidence: 99%
“…The purpose of this investigation was to evaluate prospectively whether the P-wave SAECG can predict the development of AF 3 (9%), and 4 (8%).…”
mentioning
confidence: 99%